Understanding Larry Sanders’ influence on U.S Senator Bernie Sanders (AmeriQuests, 2022)
Most Americans are familiar with the name Bernie Sanders, but few know of his brother Larry Sanders and even fewer know of the influence he has had over Bernie’s life. This commentary piece aims to understand how Larry Sanders' influence on Bernie's early life has left a lasting impact on his modern political career in the United States Senate.